Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0169915
|View full text |Cite
|
Sign up to set email alerts
|

Community Laboratory Testing for Cryptosporidium: Multicenter Study Retesting Public Health Surveillance Stool Samples Positive for Cryptosporidium by Rapid Cartridge Assay with Direct Fluorescent Antibody Testing

Abstract: Cryptosporidium is a common cause of sporadic diarrheal disease and outbreaks in the United States. Increasingly, immunochromatography-based rapid cartridge assays (RCAs) are providing community laboratories with a quick cryptosporidiosis diagnostic method. In the current study, the Centers for Disease Control and Prevention (CDC), the Association of Public Health Laboratories (APHL), and four state health departments evaluated RCA-positive samples obtained during routine Cryptosporidium testing. All samples u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
(15 reference statements)
0
8
0
1
Order By: Relevance
“…Evaluations of DNA-based syndrome panel tests have indicated high sensitivity and specificity for most targets ( 3 ). However, among pathogens for which antigen-based CIDTs are often used, such as Campylobacter and Cryptosporidium , sensitivity and specificity have varied more widely, with a large number of false positive results ( 7 , 8 ). Including CIDT positive infections to calculate incidence, some of which could be false positives, might provide an inaccurate estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of DNA-based syndrome panel tests have indicated high sensitivity and specificity for most targets ( 3 ). However, among pathogens for which antigen-based CIDTs are often used, such as Campylobacter and Cryptosporidium , sensitivity and specificity have varied more widely, with a large number of false positive results ( 7 , 8 ). Including CIDT positive infections to calculate incidence, some of which could be false positives, might provide an inaccurate estimate.…”
Section: Discussionmentioning
confidence: 99%
“…in most clinical and microbiological laboratories in Spain [ 46 ], although RLFIA is rapidly gaining acceptance as diagnostic tool due to simplicity of use and short test time. However, it is important to bear in mind that the diagnostic performance of RLFIA may be hampered by sensitivity [ 47 ], specificity [ 48 ], and reproducibility [ 49 ] issues. In our hands, the RLFIA used here delivered false-positive rates of 8.5% for G .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study we did not observe major specificity issues. Other studies have reported that RDTs were associated with a false-positive rate of 5–10% [2325], but the tests used in these studies were from different brands.…”
Section: Discussionmentioning
confidence: 99%